Model Ward dan Peppard untuk Perencanaan Strategis Sistem Informasi Bisnis Hotel - Wijang Widhiarso (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Every business always initiated by an individual or group idea in the context of seeking benefits and profits. Meanwhile, strategy is a way to realize the ideas. This research aims to find and clarify the ideas of business owners in the form of a vision, mission, and other views related to XYZ Hotel. Hotel XYZ is a two-star hotel located in Palembang City where competition with economical hotel brands and digital disruption cannot be avoided at the time this research was made, so needs a business strategy and strategy IS / IT. Based on these ideas, the authors formulate an information system strategy by evaluating the achievement indicators of ideas, analyzing business environment and IS / IT analysis, and projecting existing IS / IT to achieve the idea of ​​XYZ Hotel owner using Ward dan Peppard method.